PREPARATION OF THE FUTURE PHYSICAL EDUCATION TEACHER FOR PROFESSIONAL ACTIVITY - Козловська, Світлана (SWorldJournal, 2023)
The purpose of this article is to describe the specifics of the physical education teacher’s work in secondary school when teaching children motor actions. The basis of this research is the study of scientific literature on the selected issue, the results